2012
DOI: 10.1111/j.1582-4934.2011.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor receptor‐α cells in mouse urinary bladder: a new class of interstitial cells

Abstract: Specific classes of interstitial cells exist in visceral organs and have been implicated in several physiological functions including pacemaking and mediators in neurotransmission. In the bladder, Kit+ interstitial cells have been reported to exist and have been suggested to be neuromodulators. More recently a second interstitial cell, which is identified using antibodies against platelet-derived growth factor receptor-α (PDGFR-α) has been described in the gastrointestinal (GI) tract and has been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 45 publications
3
93
0
1
Order By: Relevance
“…at 1-2 d of age (P2). More detailed information including the protocols for assessing spinal inflammation can be found in SI Methods (23,26,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). …”
Section: Methodsmentioning
confidence: 99%
“…at 1-2 d of age (P2). More detailed information including the protocols for assessing spinal inflammation can be found in SI Methods (23,26,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). …”
Section: Methodsmentioning
confidence: 99%
“…Fundus muscularis tunica was fixed, prepared and visualized as reported previously. 21 Briefly, tissues were incubated overnight with a goat polyclonal antibody raised against c-kit (ACK2, 1:500 dilution in PBS; R&D Systems, MN, USA). Immunoreactivity was detected using Alexa-488 labeled donkey anti-goat IgG (1:500 in PBS; Molecular Probes/Invitrogen, NY, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…TCs may be nurse cells, integrating local, short-distance signals (direct contacts, exosomes and shedding vesicles) and long-distance signals through the long TPs, due to their 3D network. Recent studies have demonstrated a particular immunophenotype (34,35), distinct microRNA expression (36), specific gene-expression profiles (37) and peculiar electrophysiological properties of TCs in various organs (38). Close contact between TCs and fibroblasts was indicated in the present study.…”
Section: Discussionmentioning
confidence: 53%